2009
DOI: 10.1007/s12011-009-8511-x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Magnesium Contents in Commonly Consumed Foods and Evaluation of its Daily Intake in Korean Independent-Living Subjects

Abstract: Magnesium, an element involved in a variety of biochemical and physiological processes in the human body, is closely linked to maintaining health and preventing disease. Even so, studies on the status of magnesium intake have never been conducted sufficiently since only recently a dietary reference intake value was proposed, and data on magnesium contents in food items have always been insufficient. Therefore, in this study, we selected 366 food items commonly consumed by Korean people and then analyzed their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 7 publications
1
16
0
Order By: Relevance
“…Dietary Mg intake evaluation studies have reported that the daily Mg intake was 259.1 mg for 139 adult females aged 30-94 years [6]. In our previous study, we also reported that the daily Mg intake was 232.1 mg for females aged 19-29 years, 246.5 mg for 30-49 years, and 245.7 mg for 50-64 years.…”
Section: Introductionsupporting
confidence: 51%
See 3 more Smart Citations
“…Dietary Mg intake evaluation studies have reported that the daily Mg intake was 259.1 mg for 139 adult females aged 30-94 years [6]. In our previous study, we also reported that the daily Mg intake was 232.1 mg for females aged 19-29 years, 246.5 mg for 30-49 years, and 245.7 mg for 50-64 years.…”
Section: Introductionsupporting
confidence: 51%
“…A study assessing the Mg intake status in Spain showed that the daily intake was 256.1 mg for 1,674 females aged 25 to 60 years [19]. In South Korea, daily Mg intake was 259.1 mg for 139 females aged 30 to 94 years [6] and, in the female age group of 19-29 years, daily average Mg intake was 232.1 mg [9]. As such, Mg intake is insufficient in many countries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results obtained clearly separated S. lycopersicum cultivars from S. pimpinellifolium, S. cheesmaniae, and S. habrochaites accessions. It is necessary to emphasize a great variability of mineral and trace element content between these different tomato species, specially in Na, K, Fe, Cu, and Zn levels, although these values were in the range of other tomatoes (varieties belonging to S. lycopersicum) previously cited in literature [23][24][25][26][27].…”
Section: Resultsmentioning
confidence: 99%